(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the main features of using the case study method in teaching foreign languages. It is also pointed out that technology allows teachers to develop the creative abilities of students; develops skills in performing complex tasks in groups; helps to successfully master the ability to analyze unforeseen situations and independently develop decision-making skills.